Abstaining from annual health check-ups is a predictor of advanced cancer diagnosis: a retrospective cohort study - Yuki Kuwabara; Maya Fujii; Aya Kinjo; Yoneatsu Osaki (Komiyama Printing Co. Ltd, 2022)
Background: Cancer prevention is a crucial challenge in preventive medicine. Several studies have suggested that voluntary health check-ups and recommendations from health professionals are associated with increased participation in cancer screening. In Japan, it is recommended that individuals aged 40-74 years should undergo annual health check-ups; however, the compliance to this recommendation is approximately <50%. According to the national survey, individuals who do not undergo annual health check-ups are at a higher risk for cancer. However, to the best of our knowledge, no previous study has investigated the association between the use of health check-ups and the incidence rate of cancer. We hypothesised that not undergoing periodic health check-ups and/or less use of outpatient medical services are predictors for advanced cancer. Methods: To explore the relationship between health check-up or outpatient service utilisation and cancer incidence, this retrospective cohort study used data at two time points-baseline in 2014 and endpoint in 2017-from the National Health Insurance (NHI) claims and cancer registry. A multivariable logistic regression analysis was performed to investigate whether cancer diagnosis was associated with health check-up or outpatient service utilisation. Results: A total of 72,171 participants were included in the analysis. The results of the multivariable logistic regression showed that individuals who skipped health check-ups had a higher risk of cancer diagnosis (odds ratio [OR], 1.21; 95% confidence interval [CI], 1.04-1.40). Moreover, not undergoing health check-ups increased the risk of advanced-stage cancer (OR, 1.78; 95% CI, 1.29-2.44). Furthermore, increased rate of outpatient service utilisation was negatively associated with advanced cancer diagnosis. Conclusions: This is the first study reporting that not undergoing health check-ups is a predictor of cancer diagnosis and advanced cancer stage. Primary prevention strategies for NHI members who do not undergo health check-ups must be reassessed. Moreover, future research should examine secondary prevention strategies, such as health education and recommendations from health professionals to facilitate adequate utilisation of preventive health services.